Spatial Analysis of Changes in Land Use Against Detailed Spatial Plans (RDTR) in North Klaten District Using Geographic Information Systems (GIS) Year 2012-2020 - Agata Adi Nugroho; Agus Anggoro Sigit (Amcolabora, 2023)
The study in this study was conducted in the North Klaten District. North Klaten District was chosenbecause it has the highest population growth rate in Klaten Regency in 2012-2020. The higher thepopulation growth in an area, the higher the demand for land in the area and changes in land useoccur. A land that is continuously turned into a built-up area can lead to land use that is not inaccordance with the Detailed Spatial Plan that has been prepared by the regional government. Thisstudy aims to analyze the distribution of land use change in North Klaten District in 2012-2020 andanalyze the suitability of land use changes to the Detailed Spatial Plan for 2011-2031. The researchmethod used is a survey method to test the accuracy of digitizing data on land use changes. Thesampling method used a purposive sampling method. The analytical method used is spatial analysis todetermine the distribution of land use changes and the suitability of land use changes to the DetailedSpatial Plan. The first result of this study is the distribution of land use changes that occurred inNorth Klaten District in 2012-2020 of 158.68 ha. The highest type of land change is rice fields intosettlements of 60.05 ha or 75.69%, this land change share occurs in all villages. The village with thehighest type of change from paddy fields to settlements is Belangwetan Village, which is 10.81 ha. Thesecond result of this study is the classification of the suitability of land use changes to the DetailedSpatial Plan which is divided into two classifications, namely land changes according to the DetailedSpatial Plan of 77.17 ha or 97.26% and land changes that are not according to the Detailed SpatialPlan of 77.17 ha or 97.26% 2.17 ha or 2.74%. Changes in land use that are not in accordance withthe Detailed Spatial Plan can be caused by several factors, including the ignorance of somecommunities regarding the existence of spatial regulations and the negligence of some communities incomplying with the spatial regulations that have been set by the government in making changes toland use.